Concerning certain issues of legal regulation, goal-setting, management and work of the bank of Russia - O. V. Morozov (Plekhanov Russian University of Economics, 2019)
The Central Bank, the emission center, the reserve system, the federal treasury all these and other names are used to show the element of economy of a concrete state functioning, which controls money, i.e. estimates and administrates the money mass, buying capacity of residents in respect of goods, jobs and services, exerts influence on inflation processes and so on. The article provides results of researching the standing of normative and legal regulation, practice of using authority and responsibility, specific features of the Bank of Russia functioning as a relatively independent body of state governance and on this basis the articles studies the trends of improving management, norms of work development, procedures of working out and submitting to the State Duma of the Federal Assembly of the Russian Federation reports on federal laws bills, whose regulation is included in the competence of the Central Bank. Proposals dealing with amendments to the Federal law ‘About the Central Bank (the Bank of Russia)’ were formulated.